PENDIDIKAN DI INDONESIA DAN NEGARA BERKEMBANG LAINNYA : SEBUAH STUDI KOMPARASI - Anna Widiastuti (Universitas Islam Nahdlatul Ulama Jepara, 2004)
Education system keeps changing till nowadays, not only in developed countries, but also in developing countries. Changing in education system involves tools and equipments used also. The implementation of high technology as equipments and tools in education is a need as the speed increased used of technology. There are so many human resources marked